„Pani gruba i nieletka, gruba także portmonetka” – o dawnych i współczesnych znaczeniach (użyciach) przymiotnika gruby - Pacuła, Jarosław (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
In the article, the author presents the semantics of the lexeme gruby. He draws attention to the stages and mechanisms of shaping secondary meanings of the word (presenting changes from the Old Polish period to the present day). The analyses are based on the methods commonly adopted in lexical semantics. A special place in the considerations is given to the meaning ‘an obese, overweight person.’ The observations also concern aesthetic evaluation in language (and, partly, ethical evaluation as well), and at the same time the topic is connected with the analysis of the exponents of lexical parameterisation.